Kneeling girl, Frere temple - Ghosh, Ayan (2023)
The allegorical figure of - Charity at the Frere Temple shelters a young girl who seeks protection at her feet. The caring gesture made with her left hand is a symbol of motherly love and holding the sword with the right hand is a symbol of justice for the needy.